MONITORING OF PATIENT WITH DIABETES MELLITUS - Widodo, Widodo (Universitas Wijaya Kusuma Surabaya, 2014)
Diabetes mellitus is a disease characterized by hyperglycemia, which is caused by impaired insulin secretion, impaired insulin action, or both. Chronic hyperglycemia will lead to dysfunction and damage to various organs, such as the eyes, kidneys, nerves, heart, and blood vessels. This paper discusses the monitoring of patients with diabetes mellitus according to the laboratory tests, to know when the results of therapy has reached the optimum point as well as the prevention of complications that can occur. Â